Pengaruh Pembiayaan Mudharabah dan Pembiayaaan Musyarakah terhadap Laba Bersih Bank Syariah - Nurhamidah, Chairani; Diana, Nana (Universitas Ma'soem, 2021)
The financing income at Bank Syariah Mandiri is increasing every year and the higher the interest of the customers to carry out mudharabah financing and musyarakah financing at Bank Syariah Mandiri which will certainly make a big contribution to the bank's income. The author wants to know more about the effect of mudharabah financing and musyarakah financing on the net profit of an independent Islamic bank. The method used is a quantitative approach, using Bank Syariah Mandiri monthly financial report data for the 2017-2019 period and the number of financial reports of 36 months. The technique for selecting samples uses saturated sampling where all populations are sampled. The analysis technique uses multiple regression analysis using the SPSS 21 application.The results obtained from this study simultaneously are that there is an influence between mudharabah financing, musyarakah financing on the net profit of independent Islamic banks and partially mudharabah financing has a negative effect of 0.248 and is significant on bank net income. Syariah Mandiri and Musyarakah financing have a positive and significant effect on the net profit of Mandiri Islamic Banks.